Initial Reports of the Deep Sea Drilling Project 1982
DOI: 10.2973/dsdp.proc.64.124.1982
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Interstitial Gases in Sedimentary Deposits of the Gulf of California, Deep Sea Drilling Project Leg 64

Abstract: We analyzed interstitial gases from holes at Sites 474, 477, 478, 479, and 481 in the Gulf of California, using gas chromatography and stable isotope mass spectrometry to evaluate their composition in terms of biogenic and thermogenic sources. The hydrocarbon gas (C1-C5) concentrations were comparable to the shipboard data, and no olefins could be detected. The δ 13 C data for the CH 4 confirmed the effects of thermal stress on the sedimentary organic matter, because the values were typically biogenic near th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 6 publications
2
31
0
Order By: Relevance
“…At sub-bottom depths greater than those sampled at Leg 96 sites, ethane and other C 2 -C 5 hydrocarbons were detected (Galimov et al, 1980;Schoell, 1982). In contrast, core gas-pocket studies in the Japan Trench (Whelan and Sato, 1980), California Basin (Galimov and Simoneit, 1982), and Middle America Trench (Jeffrey et al, 1985) found C 2 -C 5 hydrocarbons at most depths where gas pockets were sampled. The processes controlling the amount of C 2 -C 5 hydrocarbons in shallow sediments containing primarily biogenic gas are unclear.…”
Section: Resultsmentioning
confidence: 88%
“…At sub-bottom depths greater than those sampled at Leg 96 sites, ethane and other C 2 -C 5 hydrocarbons were detected (Galimov et al, 1980;Schoell, 1982). In contrast, core gas-pocket studies in the Japan Trench (Whelan and Sato, 1980), California Basin (Galimov and Simoneit, 1982), and Middle America Trench (Jeffrey et al, 1985) found C 2 -C 5 hydrocarbons at most depths where gas pockets were sampled. The processes controlling the amount of C 2 -C 5 hydrocarbons in shallow sediments containing primarily biogenic gas are unclear.…”
Section: Resultsmentioning
confidence: 88%
“…The presence of both authigenic and detrital components was also noted in the types of organic matter found in the sediments Simoneit and Philp, 1982;Gilbert and Summerhayes, 1982;Galimov and Simoneit, 1982).…”
Section: Contact Metamorphic Processesmentioning
confidence: 82%
“…Interstitial gas contains light hydrocarbons indicative of thermogenesis with very negative δ 13 C (Whelan and Hunt, 1982;Galimov and Simoneit, 1982;Simoneit and Galimov, 1984). Bitumen fractions and the makeup of the n-alkenes similarly indicate high levels of thermogenic alteration of the sediments at DSDP Site 477 .…”
Section: Contact Metamorphic Processesmentioning
confidence: 99%
See 2 more Smart Citations